Proposal for a unified CCN nomenclature. Issue 2 (1st April 2003) - Brigstock, D R; Goldschmeding, R; Katsube, K-i; Lam, S C-T; Lau, L F; Lyons, K; Naus, C; Perbal, B; Riser, B; Takigawa, M; Yeger, H
Abstract : A proposal is put forth to unify the nomenclature of the CCN family of secreted, cysteine rich regulatory proteins. In the order of their description in the literature, CCN1 (CYR61), CCN2 (CTGF), CCN3 (NOV), CCN4 (WISP-1), CCN5 (WISP-2), and CCN6 (WISP-3) constitute a family of matricellular proteins that regulate cell adhesion, migration, proliferation, survival, and differentiation, at least in part through integrin mediated mechanisms. This proposal is endorsed by the International CCN Society and will serve to eliminate confusion from the multiple names that have been given to these molecules.